Public awareness of colorectal cancer in Saudi Arabia: A survey of 1070 participants in Riyadh - Ahmad M Zubaidi; Noura M AlSubaie; Areej A AlHumaid; Shaffi A Shaik; Khayal A AlKhayal; Omar A AlObeed (The Saudi Journal of Gastroenterology, 2015)
Background/Aims: The aim of this study was to investigate colorectal cancer (CRC) awareness in healthy individuals in Saudi Arabia in order to identify segments of the population that would most benefit from targeted education programs. Setting and Design: Survey/questionnaire. Patients and Methods: Random, healthy individuals from Riyadh, Saudi Arabia, were approached to participate in a 10-question multiple choice survey about CRC. Data were analyzed by demographic criteria, including age, gender, marital status, and level of education, to determine if members of these groups displayed differential knowledge. Statistical Analysis: Differences in responses by demographic data were analyzed using Pearson′s Chi-square test. A P < 0.05 was considered statistically significant. Results: In total, 1070 participants completed the survey. Most respondents believe that screening for colon cancer should begin at symptom onset (42.9%). Less than 20% of all respondents believe that polyps are a risk factor for CRC, which varied significantly according to level of education; however, even the most educated answered correctly less than 50% of the time. Similarly, only 34.8% of all respondents knew that a family history of CRC imparted a personal risk for CRC. Conclusions: Although older individuals and those with higher education tended to answer questions correctly more often, there were some misconceptions regarding universally accepted screening protocols, symptoms, and general understanding of CRC in Saudi Arabia. A national education/screening program in Saudi Arabia is recommended to improve CRC knowledge.